KEKUATAN LAKI-LAKI “DI BAWAH KETIAK PEREMPUAN”: MEMBANGUN PERSPEKTIF GENDER DI SUMATERA BARAT - Reza Fahmi (Kafa`ah: Journal of Gender Studies, 2013)
The Minangs are the world's largest matrilineal society; properties such as land and houses are inherited through female lineage. Some scholars argue that this might have caused the diaspora (Minangkabau, "merantau") of Minangkabau males throughout the Maritime. The native Minangkabaus agreed that this matrilineal culture is indeed the result of (not the reason for) diaspora. Theoriticaly male have a lot of power. They had responsible to protect their fanily wealth as one example.  But unfortunoutly, their possition in“underarm of women”. All kinds of dicission should be get confirm from the women (“so-called”: Bundo Kandung). It means that we should re-thinking about gender perspective in Minangkabau community, because female dominate the power. Keywords : Minangkabau People, Matriarchy, Gender RelationCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.72